Stones and Power in the Kelapang: Indigeneity and Kelabit and Ngurek Narratives - Valerie, Mashman (Springer, Singapore, 2017)
There are traces of early settlement in the lower Kelapang River in Sarawak, Borneo indicated through stone graves, menhirs and stone mounds. Recollections of histories of these sites by the local Christian Kelabit population are hazy, and until the recent resurgence of interest in the stone culture in the area, people were reluctant to visit these places as they were associated with death and the spirit world. A contemporary Kelabit narrative outlines previous occupation of the area with the Ngurek as ‘our people’, and paradoxically states that the Kelabit alone built the stone monuments. This in line with other claims in the highlands of an exclusive association with the stone culture, and can be understood as one of latent indigeneity as it highlights attachment to territory and excludes other groups. Parallel Ngurek narratives in circulation link their settlement in the Kelapang to a time when the Ngurek had supernatural power that enabled them to cut stone. These stories also explain the loss of this supernatural power, the decline of the culture of stone grave and mounds, and the reduction of their population after the Ngurek community left the area. Exploring the gap between parallel accounts of histories in the area creates a future opening for a more dynamic heterogeneous history of the Kelabit highlands and the stone culture. This indicates a need for reconsideration of notions of indigeneity and identity.